Adaptasi Alat Ukur Breakup Distress Scale Versi Bahasa Indonesia - Wisnuwardhani, Adelin Rizkyka; Susanto, Hery (Universitas Batanghari Jambi, 2025)
This research aims to adapt, test and evaluate the validity and reliability of the adaptation of the Indonesian version of the Breakup Distress Scale measuring tool. The research was carried out by adapting instruments using international measuring instrument adaptation guidelines from the International Test Commission (ITC). Data collection was carried out online using Google form, using convenient sampling techniques. Based on the calculation results, the adaptation of the Indonesian version of the Breakup Distress Scale meets the criteria and is quite good.